Pengaruh Sistem Tanam Vertikultur dan Jarak Tanam terhadap Pertumbuhan Vegetatif Dua Kultivar Tanaman Kedelai Hitam (Gylcine max L.) - Rati Purnama Harahap; Rahmadina Rahmadina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the effect of the verticulture system and spacing on the vegetative growth of two cultivars of black soybean (Gylcine max L.). This study used a factorial randomized block design (RBD) with two treatment factors and 4 replications, namely F1= cultivar (P) consisting of two levels, namely P1= soybean cultivar Detam 1 and P2 = soybean cultivar Detam 4 Prida. F2= plant spacing consists of two levels, namely J1= 20 x 10 cm and J2= 20 x 20 cm. The parameters used were plant height, leaf area index, chlorophyll a, b and total content, relative growth rate, net assimilation rate, and number of root nodules. The results obtained from this study plant spacing had a significant effect on several parameters with the best level, namely J2= 20 x 20 cm and soybean cultivars with P1= detam 1 level had a significant effect on plant height parameters. But the plant spacing and the two soybean cultivars (Gylcine max L.) did not have any interaction in each parameter. It can be concluded that the regulation of planting distances and two soybean cultivars has a significant effect on several parameters such as plant height, chlorophyll content tests a, b and total as well as measuring relative growth rates. Keywords: Black Soybean, Plant Spacing and Verticulture